Bindius triquetrus gen. nov. sp. nov. (Eutardigrada, Hypsibiidae) from Sicily (Italy) - Pilato, Giovanni (Zootaxa, 2009)
A new species is described for which a new genus, Bindius gen. nov., is also instituted. This new genus belongs to the family Hypsibiidae. The claws are of the Hypsibius type; the bucco-pharyngeal apparatus is of the Diphascon model (i.e., with an anterior rigid buccal tube and a posterior, flexible pharyngeal tube), and it is a variant of the Diphascon type; it is characterized by large apophyses for the insertion of the stylet muscles, asymmetrical with respect to the frontal plane for shape and dimensions; the dorsal apophysis is triangular in shape with rectilinear dorsal margin and posterior apex very distant from the buccal tube wall; the ventral apophysis is similar to the one of Diphascon, i.e., in the shape of a semilunar hook, but larger. The new species, Bindius triquetrus sp. nov., has smooth cuticle; eye spots absent; elongated pharyngeal bulb with small apophyses and three long, rod-shaped macroplacoids; a small, very faint, microplacoid may be present; septulum absent; claws slender; lunules and other cuticular thickenings on the legs absent.